A paradigm shift in German family policy: Applying a topic model to map reform and public discourse, 1990–2016. (8th October 2019) - Gülzau, Fabian
Abstract: This article explores the newspaper discourse surrounding a paradigm shift in social policy. The case at hand, Germany, is a prime example of a welfare state that was particularly resistant to reform. Hence, the rapid paradigm shift in German family policy since the late 1990s is puzzling. This study seeks to resolve this puzzle by drawing on the insight that public discourse is crucial for policy change. Politicians have to promote reforms prior to their implementation. The main channel for communication with the wider public is the mass media. I use newspaper coverage from 1990 to 2016 to analyze whether the media is responsive to reform initiatives. I use topic modeling, an innovative method from the computational social sciences (CSS), to identify dominant themes and shifts over time in a large corpus of newspaper articles ( N = 1, 459). The analysis shows that public discourse was responsive to the parliamentary debate. The article also clarifies the role of critical events and identifies discursive strategies. 摘要: 本文探究了围绕社会政策范式转变的报刊话语。作为特别抵制改革的福利国，德国是一个典型案例。正因如此，自20世纪90年代末起德国家庭政策发生的快速范式转变显得难以理解。本研究通过利用公共话语对政策转变至关重要这一见解，试图解决该疑问。政客需在执行改革之前对其进行宣传。与更广范围的公众进行沟通的主要渠道是大众媒体。作者使用1990年至2016年间的报刊报道来分析媒体是否会响应改革倡议。作者使用主题建模，一种源于计算社会科学（CSS）的创新方法，来识别一个大型的报刊文章语料库（N=1, 459）中随时间推移而出现的热门主题和转变。分析显示，公共话语曾响应过议会辩论。本文还阐明了关键事件的作用，识别了话语性策略。 Resumen: Este artículo explora el discurso periodístico en torno a un cambio de paradigma en la política social. El caso en cuestión, Alemania, es un excelente ejemplo de un estado de bienestar que fue particularmente resistente a la reforma. Por lo tanto, el rápido cambio de paradigma en la política familiar alemana desde finales de la década de 1990 es desconcertante. Este estudio busca resolver este enigma basándose en la idea de que el discurso público es crucial para el cambio de políticas. Los políticos tienen que promover reformas antes de su implementación. El principal canal de comunicación con el público en general son los medios de comunicación. Utilizo la cobertura periodística de 1990 a 2016 para analizar si los medios responden a las iniciativas de reforma. Utilizo el modelado de temas, un método innovador de las ciencias sociales computacionales (CSS), para identificar temas dominantes y cambios a lo largo del tiempo en un gran corpus de artículos periodísticos (N = 1, 459). El análisis muestra que el discurso público respondía al debate parlamentario. El artículo también aclara el papel de los eventos críticos e identifica estrategias discursivas.